3D-CFD Simulation of Confined Cross-Flow Injection Process Using Single Piston Pump - Elashmawy, M. (Engineering, Technology & Applied Science Research, 2017)
Injection process into a confined cross flow is quite important for many applications including chemical engineering and water desalination technology. The aim of this study is to investigate the performance of the injection process into a confined cross-flow of a round pipe using a single piston injection pump. A computational fluid dynamics (CFD) analysis has been carried out to investigate the effect of the locations of the maximum velocity and minimum pressure on the confined cross-flow process. The jet trajectory is analyzed and related to the injection pump shaft angle of rotation during the injection duty cycle by focusing on the maximum instant injection flow of the piston action. Results indicate a low effect of the jet trajectory within the range related to the injection pump operational conditions. Constant cross-flow was used and injection flow is altered to vary the jet to line flow ratio (QR). The maximum jet trajectory exhibits low penetration inside the cross-flow. The results showed three regions of the flow ratio effect zones with different behaviors. Results also showed that getting closer to the injection port causes a significant decrease on the locations of the maximum velocity and minimum pressure.